2019
DOI: 10.3389/fmicb.2019.00775
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a 16th Century Traditional Chinese Medicine Use of Ginkgo biloba as a Topical Antimicrobial

Abstract: In the search for new therapeutic solutions to address an increasing number of multidrug-resistant bacterial pathogens, secondary metabolites from plants have proven to be a rich source of antimicrobial compounds. Ginkgo biloba , a tree native to China, has been spread around the world as an ornamental tree. Its seeds have been used as snacks and medical materials in Traditional Chinese Medicine (TCM), while over the last century its leaf extracts emerged as a source of rising pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Ginkgolic acid has been studied relatively extensively for its therapeutic effects on cryptosporidiosis [57,58], human immunodeficiency virus (HIV) and HIV infection [59], hypertension [60,61] and cancer [56,62]. Furthermore, G. biloba L. has long been used in traditional Chinese medicine for treating lung and skin diseases [63,64], and its extracts have been assessed also as a remedy for cognitive impairment treatment in people [65,66]. Based on the licenced use of G. biloba extracts [65] and the selective toxicity of ginkgolic acid, it is possible that compound 4 and related compounds from algae, such as S. decipiens, might exert toxic effects selectively towards parasitic cells over mammalian host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgolic acid has been studied relatively extensively for its therapeutic effects on cryptosporidiosis [57,58], human immunodeficiency virus (HIV) and HIV infection [59], hypertension [60,61] and cancer [56,62]. Furthermore, G. biloba L. has long been used in traditional Chinese medicine for treating lung and skin diseases [63,64], and its extracts have been assessed also as a remedy for cognitive impairment treatment in people [65,66]. Based on the licenced use of G. biloba extracts [65] and the selective toxicity of ginkgolic acid, it is possible that compound 4 and related compounds from algae, such as S. decipiens, might exert toxic effects selectively towards parasitic cells over mammalian host cells.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with other extract tested against C. acnes biofilm disruption, H. odoratissimum showed prominent activity. A study by Chassagne et al (2019) reported the biofilm eradication concentration (MBEC 50 ) of Gingko biloba seed nut extract against C. acnes at 256 μg/ml and an MIC of 64 μg/ml.…”
Section: Biofilm Prevention and Disruptionmentioning
confidence: 99%
“…Ginkgo ( Ginkgo biloba L.) is a well-known relict plant that originates from China and has been described as a “living fossil” [19]. As a multifunctional tree species, ginkgo has important economic and medicinal values [20] and has attracted researchers’ attention with many studies have been reported on the origin and evolution, cytology, molecular biology, tree breeding and medicinal value of ginkgo [19, 2125]. Ginkgo is also a popular ornamental species and widely cultivated worldwide [24].…”
Section: Introductionmentioning
confidence: 99%